2017
DOI: 10.3389/fpls.2017.01954
|View full text |Cite
|
Sign up to set email alerts
|

A Novel QTL for Powdery Mildew Resistance in Nordic Spring Barley (Hordeum vulgare L. ssp. vulgare) Revealed by Genome-Wide Association Study

Abstract: The powdery mildew fungus, Blumeria graminis f. sp. hordei is a worldwide threat to barley (Hordeum vulgare L. ssp. vulgare) production. One way to control the disease is by the development and deployment of resistant cultivars. A genome-wide association study was performed in a Nordic spring barley panel consisting of 169 genotypes, to identify marker-trait associations significant for powdery mildew. Powdery mildew was scored during three years (2012–2014) in four different locations within the Nordic region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…Our GWAS results showed that there was a major QTL found in chromosome 4H associated with powdery mildew resistance. A similar study reported that a QTL associated with mlo alleles was identified on chromosome 4H 30 , which was also verified in the current study (Fig. 4A).…”
Section: Gwas To Identify Snps Associated With Traits In Spring Barlesupporting
confidence: 92%
“…Our GWAS results showed that there was a major QTL found in chromosome 4H associated with powdery mildew resistance. A similar study reported that a QTL associated with mlo alleles was identified on chromosome 4H 30 , which was also verified in the current study (Fig. 4A).…”
Section: Gwas To Identify Snps Associated With Traits In Spring Barlesupporting
confidence: 92%
“…One option for breeding barley, especially winter cultivars, against powdery mildew attack is accumulating (pyramiding, stacking) nonhypersensitive, nonspecific quantitatively inherited resistance genes [ 110 , 115 , 116 , 117 , 118 ] originating from cultivars as well as landraces [ 119 ] and wild barley [ 97 , 98 , 120 , 121 , 122 , 123 , 124 ]. Although not all quantitative genes are necessarily nonspecific, this way shows promise.…”
Section: The Future Beyond Specificitymentioning
confidence: 99%
“…A barley panel of 490 genotypes, consisting of progenies and founders from four multi-parent populations, was investigated in this study. The founders consisted of cultivars (9), breeding lines (4) and landraces (4) ( Table 1 ) with desirable traits for diseases such as scald, leaf rust, Fusarium and spot form of net blotch and PM [ 62 ]. One goal was to pyramid resistances into adapted background.…”
Section: Methodsmentioning
confidence: 99%